A humanização da pessoa surdocega pelo atendimento educacional : contribuições da psicologia histórico-cultural - Sierra, Maria Angela Bassan (2010)
This work has arisen from a bibliographical research study (Post-Graduate Psychology Programme - UEM, 2008-9). The publications that were selected as primary sources included Russian and Soviet authors such as L.S.Vygotsky, I.Sokolyansky and A.Meshcheryakov, and the Dutch author Jan Van Dijk and the tudy also drew on papers from the Brazilian Ministry of Education. In the case of secondary sources, the study particularly relied on publications that discussed or commented on the authors and papers mentioned above. The main aims of the study are as follows: to broaden the scope of the study into examining the importance of schooling in the process of humanising the deaf-blind; to understand the contribution made by historico-cultural theories in caring for the needs of deaf-blind people; to define the current situation with regard to the state of deaf- blindness; and to explain and discuss pedagogical issues and participatory action taken with those suffering from deaf-blindness - such as that taken by the Soviet authors. With regard to the researcher, the reason for conducting this investigation is partly explained by her professional career interests but mainly by the current situation in Brazil, where there are 413 deaf-blind people enrolled in courses out of a total of 65,515 people with this handicap. In the face of the need for more aid and support so that thought can be given to their education, a step back has been taken to consider how Soviet defectology in its search for a clarification of ways of caring for the deaf-blind compares with the ideas of Jan Van Dijk, the author on whom the policies of the Brazilian government are based. Thirty-four texts were found in the specialist libraries related to this area of research. It was clear that the Soviet policy began with the work of humanising the deaf-blind through everyday activities that were full of significance and not simply training exercises. By means of this approach, working with toys, modelling or other resources, the work acquired a social character, a feature that can be understood as something that goes beyond simply encouraging a close familiarity with other people, and forms the basis for a socialist ideal. Verbal language (governed by the alphabet, based on Braille, and using signals and finger-spelling among other means) as warmly recommended by Vygotsky, was an essential tool in the path to becoming humanised and it is through this means that the educational process must occur. In the view of Van Dijk, (although not well-known for any political tendencies) communication is also of vital importance, and he sought to provide skills or help in the renewal of skills of deaf-blind people, who had contracted German measles at the beginning of the 1960s. Van Dijk worked out his theories on the basis of a collaborative approach in which the deaf-blind person is always carrying out his activities together with someone else (a teacher, carer or acquaintance etc) and passes through six stages. As a result, I draw attention to the importance of schooling for the deaf-blind person as a way of escaping from isolation and becoming humanised and lay stress on the fact that educational experiments can and should be undertaken, although the ethical standards underpinning them, must also be supported by theoretico-philosophical principles and methodological guidelines that are compatible with each other. In my view, as well as having a policy aimed at the deaf-blind person, it is necessary to invest in theoretical-methodological training which does not exclude history and philosophy from the teachers and deaf-blind students. Good training of this kind can provide an opportunity for educational work to be carried out, in such a way that it leads to building up a consciousness in deaf-blind people, of what is distinctively human.